The effect of rare earth element segregation on grain boundary energy and mobility in magnesium and ensuing texture weakening. (15th March 2018) - Barrett, Christopher D.; Imandoust, Aidin; El Kadiri, Haitham
Abstract: This paper elucidates a key puzzle related to texture randomization - effect of rare earth on grain boundaries. We use electron back-scatter diffraction and molecular dynamics to compare recrystallization between pure Mg and a Y-containing alloy. The alloy's texture components were initially similar, but the large ⟨ a ⟩ fiber grains in pure Mg overtook all other components. Y segregation homogenized the energies of ⟨ a ⟩ fiber grain boundaries, curtailing conventional recrystallization. Grain boundary mobilities were reduced proportionally to the energy stabilization, reducing the dominance of 10 1 ¯ 0 extrusion texture. This allows other grain orientations to stabilize thus producing a more randomized texture. Graphical abstract: